Verification of a large-band metamaterial absorber and its application in the measurement of thermal properties of clothing fabrics - Ge Huang; Min Zhong; Nanguang Su (Materials Research Express, 2022)
The development and application of smart fabrics is a research hotspots in clothing fabrics. Accurately measuring the thermal conductivity of clothing fabric samples is an important basis for developing corresponding products. Here, thermal properties (thermal resistance and diffusivity) of clothing fabrics were measured through using a metamaterial sensor. The measured thermal resistance and diffusivity of the clothing fabrics could be affected by ambient temperature. The measured thermal resistance was also enhanced by increasing the fabric sample thickness. Similar resonance behaviors could be found in the fitted results based on the heat conduction theory. Finally, under the condition of the same thickness and temperature, the thermal properties of four clothing fabric samples were simulated and measured.